THE IMPACT OF ACCOUNTING CONSERVATISM ON ENTERPRISE INNOVATION INVESTMENT (International journal of artificial intelligence, 2025)
This study explores the effect of accounting conservatism on corporate innovation investment, using the information asymmetry theory as a framework. While existing literature acknowledges the role of accounting conservatism in corporate decision-making, there is limited understanding of how it specifically impacts innovation investment, particularly in different market and regulatory environments. Current research often neglects how the impact of accounting conservatism on innovation investment varies across these contexts. Additionally, studies focusing on Uzbekistani listed companies are scarce. This study addresses these gaps by analyzing data from Uzbekistani A-share listed companies, revealing a negative relationship between accounting conservatism and corporate innovation investment.